The Influence of Self-determined Motivation and Goals of International Students to Study Abroad on Subjective Well-Being: The Mediating Role of Psychological Needs Satisfaction and the Moderating Role of Socio-Cultural Adjustment - Muthuswamy, Vimala Venugopal (Journal of International Students, 2023)
The primary objective of this study was to examine the potential impact of self-determined motivation on the satisfaction of psychological needs and, subsequently, the subjective wellbeing of international students. Additionally, the present study sought to investigate the correlation between students’ aspirations to pursue international education and their level of psychological need fulfilment. In addition to this, the study sought to examine the moderating influence of sociocultural adjustment on the relationship between psychological needs satisfaction and subjective wellbeing among international students. In order to accomplish this objective, a combination of convenience sampling and survey methods was employed to select a sample of 267 international students who were enrolled in various universities within Saudi Arabia. The data that was gathered was subjected to analysis using statistical software programmes such as SPSS and AMOS. This analysis aimed to examine both direct and indirect effects, encompassing concepts such as mediation and moderation. The findings of the study indicate a positive correlation between the fulfilment of psychological needs and the subjective well-being of international students enrolled in different universities in Saudi Arabia.